Odpowiedzi

2010-01-13T22:13:18+01:00
E) =3x³-15x-6-2x³+2x²+2x-8=x³+2x²-13x-14

f) =x³-2x²-5x-3x³+12x²-6x+3=-2x³-10x²-11x+3

g) =2x⁴-10x³-12x²+4x⁴-8x³-4x²-28=6x⁴-18x³-16x²-28

h) =14x²-6x-35x+15=14x²-41x+15

a) =-2x³+4x²-2x-3+1-3x-5x²-x³-2+4x-x³= -4x³-x²-x-4

b) =x⁴-4x³-5x²-3x+2-2x⁴-4x²+3x-2-2+3x²-x³-x⁴=-2x⁴-5x³-6x²-2

c) =3x³-5x-3-2x+x³+x-2x²+x³=5x³-2x²-6x-3

d) =3-2x³+3x²+4x-3-2x³-4x²+3=-4x³-x²+4x+3

i) =4x⁴+8x-10x²-20x-6x-12=4x⁴-10x²-18x-12

j)=x⁴+x³+3x²-2x³-2x²-6x-x²-x-3=x⁴-x³-7x-3

k) =3x⁴-12x²+6x+2x²-8x+4-x⁴+2x²-4x³+4x-4x²+8=2x⁴-4x³-12x²+2x+12

l) =[2x²-4x-2-3(x²+2x-3)](2x+1)=[2x²-4x-2-3x²-6x+9](2x+1)=[-x²-10x+7](2x+1)=-2x³-x²-20x²-20x+14x+7=2x³-21x²-6x+7

m) =8x³-1-(9+x²)(x+1)=8x³-1-9x-9-x³-x²=7x³-x²-9x-10

n) =4(2x²+x⁴-4-x²)-(9+x²)(x+1)=8x²+4x⁴-16-4x²-9x-9-x³-x²=4x⁴-x³-3x²-9x-25

o) =27x³+18x²+12x-18x²-12x-8-2(-x³-64)=27x³-8+2x³+128=29x³+120
1 5 1